العلة النحوية في إعراب الفعل المضارع (دراسة نحوية تحليلية) - Fachiroh, Wirdah (Al-Zahra: Journal for Islamic and Arabic Studies, 2023)
This study aims to show the greatness of the Arabic language, by searching for the grammatical vowel, which is part of the study of the origins of grammar. Inflection, and it has a special sign of inflection, which is assertiveness. Also, it is not permissible to enter the preposition that is the special sign of inflection for nouns, and it is necessary to study the grammatical cause of this issue in order to reveal the secrets and phenomena of the Arabic language that were developed by linguists and grammarian. This study relies on the descriptive, analytical and comparative approach, and the researcher collects the sayings of grammarians from the most important grammatical books in the chapter on the reason for the inflection of the presenttense, such as the book by Sibawayh.The grammatical arguments of al-Zujaji, the characteristics of Ibn Jinni, the insight and the remembrance of al-Saimar, the explanation of the detailed explanation of Ibn Ya’ish, the explanation of the facilitation of Ibn Malik, and the memorization of al-Hawami’ by al-Suyuti. Then you analyze it and compare these sayings and make comments and weighting                                                                                                                                                                    The result of this research is that the grammatical reason has indicated the richness of the Arabic language and the eloquence of its people and revealed the Arabic secrets, especially in understanding the inflection of the present tense and its reason in being specialized in assertiveness and not entering the preposition in it